Effects of starvation and viscous shear heating in hydrodynamically lubricated rolling/sliding line contacts - Anandan N.; Pandey R.K.; Jagga C.R.; Ghosh M.K. (My University, 2025)
Combined effects of viscous shear heating and starvation in hydrodynamically lubricated high-speed rolling/sliding line contacts have been investigated numerically by using an efficient computational method for the solution of energy equation in which temperature distribution across the film is approximated by Legendre polynomial. Effects of starvation on minimum film thickness, traction coefficient, and mid-film temperature rise are computed for lightly loaded, lubricated rolling/sliding line contacts. Lubricant starvation in the contact has been created by gradually reducing the length of the computational domain from the inlet side. The performance parameters in the line contact have been evaluated for high-rolling speeds (15-45 m/s), light loads (10 × 103 - 17 × 103 N/m), and slip values varying up to 10 per cent. Significant reduction in minimum film thickness, traction coefficient, and maximum mid-film temperature rise has been observed with the increase in the severity of starvation. The analysis reveals that the existence of starvation seems to be beneficial in terms of reduced traction and temperature rise provided there is a continuous film at the contact. On the basis of this work, empirical relations are developed for the prediction of non-dimensional minimum film thickness, traction coefficient, and non-dimensional maximum mid-film temperature rise in the contact in terms of various operational parameters viz. thermal loading parameter (Q), non-dimensional load (W), slip (S), and starvation parameter ( Xs ). © IMechE 2006.